2021
DOI: 10.1002/hed.26824
|View full text |Cite
|
Sign up to set email alerts
|

Fact or fiction?”: Oral cavity cancer in nonsmoking, nonalcohol drinking patients as a distinct entity—Scoping review

Abstract: Oral cavity cancer is often described as a lifestyle‐related malignancy due to its strong associations with habitual factors, including tobacco use, heavy alcohol consumption, and betel nut chewing. However, patients with no genetically predisposing conditions who do not indulge in these risk habits are still being encountered, albeit less commonly. The aim of this review is to summarize contemporaneous reports on these nonsmoking, nonalcohol drinking (NSND) patients. We performed database searching to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(302 reference statements)
0
5
0
Order By: Relevance
“…Although various other possible mechanisms attributed to alcoholic mouth use has been extensively researched, at least two recent systematic review and meta analysis concluded that there is significant lack of evidence to directly implicate alcoholic mouth rinses in oral cancer pathogenesis 16,17 . As noted in our recently published scoping review, it is worth acknowledging that oral cancer in non‐smoking, non‐alcohol drinking patients is in fact a distinct entity unrelated to HPV infection 18 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although various other possible mechanisms attributed to alcoholic mouth use has been extensively researched, at least two recent systematic review and meta analysis concluded that there is significant lack of evidence to directly implicate alcoholic mouth rinses in oral cancer pathogenesis 16,17 . As noted in our recently published scoping review, it is worth acknowledging that oral cancer in non‐smoking, non‐alcohol drinking patients is in fact a distinct entity unrelated to HPV infection 18 …”
Section: Introductionmentioning
confidence: 94%
“…16,17 As noted in our recently published scoping review, it is worth acknowledging that oral cancer in nonsmoking, non-alcohol drinking patients is in fact a distinct entity unrelated to HPV infection. 18 Various studies have been carried out globally to assess the awareness of both patients and oral health professionals (OHPs) regarding OSCC and PMD. In a recent Australian study involving dentists, dental specialists, hygienists, dental and oral health therapists it was noted that, although 95% supported regular OSCC screening, only 51% actually performed screening in practice.…”
Section: Australian Dental Journalmentioning
confidence: 99%
“…It has been demonstrated that the combination of alcohol and smoking increases the risk in a synergic way, so that the probability of HNC onset increases dramatically when these two factors coexist [ 80 , 81 , 82 , 83 ]. On the other hand, the beneficial impact of cessation of alcohol consumption and tobacco smoking, as well as the protective effect of fruit and salad intake, which may modulate the deleterious effects of tobacco and alcohol, has been demonstrated [ 84 , 85 , 86 , 87 , 88 ]. Recently, it has been suggested that non-smoking and non-drinking oral SCC patients may represent a different entity with a limited role for HPV infection in carcinogenesis, but also that they are associated with worse outcomes when expressing HPV16 [ 89 , 90 ].…”
Section: Head and Neck Cancer Etiopathogenesismentioning
confidence: 99%
“…One-hot transformation of the smoking and alcohol-consumption risk-habit categories was performed to engineer a new feature that differentiated patients into non-smoking, non-alcohol-drinking (NSND) patients and smoking and alcohol-drinking (SD) patients. The rationale for this stratification has already been described by our group and others [ 21 , 22 ]. No data transformation or feature engineering was performed with other categorical input features.…”
Section: Methodsmentioning
confidence: 99%